2015
DOI: 10.1002/macp.201400545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyphosphazene Derivatives via Thiol‐ene Click Reactions in an Aqueous Medium

Abstract: A green route is reported for functionalizing polyphosphazene via the thiol-ene click reaction in an aqueous medium. Poly[bis(allylamino)phosphazene] is used as the precursor polymer, which is easily dissolved in water containing 5% (v/v) phosphoric acid, but barely dissolved in other acidic aqueous solutions with the same pH value. Three thiol reagents, namely, 3-mercapto-1,2-propanediol, 2-mercaptoethoxy ethanol, and L -cysteine, are then reacted with the precursor in the phosphoric acid aqueous solutions. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The addition of 1-thioglycerol via photochemical thiol–yne addition led to a star-shaped hydroxyl-polyphosphazene (polymer 2 ). The thiol–yne addition method provides a fast and convenient alternative for the insertion of thio-glyceryl moieties onto a [NPCl 2 ] n backbone, 29 which otherwise would require extensive protecting group strategies. 30 The substitution of two groups per alkyne moiety further multiplies the functional groups to eight per phosphazene repeat unit.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The addition of 1-thioglycerol via photochemical thiol–yne addition led to a star-shaped hydroxyl-polyphosphazene (polymer 2 ). The thiol–yne addition method provides a fast and convenient alternative for the insertion of thio-glyceryl moieties onto a [NPCl 2 ] n backbone, 29 which otherwise would require extensive protecting group strategies. 30 The substitution of two groups per alkyne moiety further multiplies the functional groups to eight per phosphazene repeat unit.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The NMR data were in full agreement with those reported. To obtain a water-based solution of CPZ, the method of Qian et al [76,77] for allylamino-polyphosphazenes was adopted, which proved that the phosphazenes remained stable under acid conditions. Therefore, the solubility of the CPZ was tested in different aqueous acids (H 3 PO 4 , H 2 SO 4 , HCl).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, an allylamino cyclotriphosphazenes (CPZ) was synthesized and tested with regard to its efficiencies as a flame retardant for CO, PET, PA, and CO/PET- or COPA-blended textiles in the presented study. Inspired by the work of Qian et al [76,77] who demonstrated thiol-ene reactions in water with allylamine and propargylamine polyphosphazenes, water-soluble cyclotriphosphazene derivatives were thus adapted for textile finishing. Up to now, no work has been reported on the utilization of CPZ as a green flame retardant in water-based finishing protocols of textiles.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers cover a broad range of materials with tunable cytocompatibility and biodegradability, and thus the following discussion is centered on these PPZs. A considerable number of organic side chains have been introduced in PPZs, including amino acid esters, peptides, saccharides, arylcarboxylates, ethylene oxide/PEG, and other biomolecules (purine and pyrimidine bases, vitamins, etc.) .…”
Section: Part I Background and Fundamental Properties Of Ppzmentioning
confidence: 99%